Gender, wages and social security in China's industrial sector - Johanna Rickne (Uppsala University, Department of Economics, 2010)
This study compares average earnings and productivities for men and women employed in roughly 200,000 Chinese industrial enterprises. Women's average wages lag behind men's wages by 11%, and this result is robust to the inclusion of non-wage income in the form of social insurance payments. The gender-wage gap is wider among workers with more than 12 years of education (28%), mainly because of the higher relative wages received by skilled men in foreign-invested firms. Women's average productivity falls behind men's productivity by a larger margin than the gap in earnings, and the null-hypothesis of earnings discrimination is thereby rejected. Equal average wages between men and women are found among firms located in China's Special Economic Zones, and also among some light industrial sectors with high shares of female employees. Market reform hence appears to have improved women's relative incomes.
urn:nbn:se:uu:diva-125153
Keywords: I30; J16; J71; O10; 330; China; gender wage gap; non-wage compensation; Fraueneinkommen; Betriebliche Sozialleistungen; Geschlechterdiskriminierung; Industrie; China